RESISTENSI GENDER CALON KEPALA DAERAH - Suwardi, - (Transformasi, 2015)
Gender ideology especially in local political life is still dominant. Various cases of election in the province of Central Java in particular. This study lasted noted few major woman candidates who successfully won the election. Studi been performed in various local election in the province of Central Java, among others Sukoharjo Regency (2010 ); Sragen Regensi (2010); Klaten Regency (2010); Demak Regency (2010), Pati Regency (2011); Pekalongan Regency (2011); Major woman candidates have additional obstacles to win the elections, namely gender resistance.Keyword: local election, resistance, gender.